A Framework for Global Twenty-First Century Scenarios and Models of Biological Invasions. (31st July 2019) - Lenzner, Bernd; Leclère, David; Franklin, Oskar; Seebens, Hanno; Roura-Pascual, Núria; Obersteiner, Michael; Dullinger, Stefan; Essl, Franz
Abstract: Biological invasions have emerged as an eminent feature of global change, with substantial impacts on the environment and human livelihoods. Current research demonstrates that the numbers and impacts of alien species are rising unabatedly. At the same time, we lack a thorough understanding of potential future trajectories for the decades to come. With the recent establishment of comprehensive global databases, it is, for the first time, feasible to develop and quantify future scenarios of biological invasions. Therefore, we propose a conceptual framework for how to develop alien species scenarios for the twenty-first century and how to identify relevant steps and challenges along the way. The concept will be important to inform research, policy, stakeholders, and the general public. Furthermore, we call for the scientific community to join forces and to operationalize the framework for scenarios and models of biological invasions to develop an important baseline for understanding and managing future biological invasions.